Reconstruction for multi-wave imaging in attenuating media with large damping coefficient. (15th November 2016) - Palacios, Benjamín
Abstract: In this article we study the reconstruction problem in TAT/PAT on an attenuating media. Namely, we prove a reconstruction procedure of the initial condition for the damped wave equation via Neumann series that works for arbitrary large smooth attenuation coefficients extending the result of Homan in (2013 Inverse Problems Imaging 7 1235–50 ). We also illustrate the theoretical result by including some numerical experiments at the end of the paper.